2020
DOI: 10.1111/joim.13018
|View full text |Cite
|
Sign up to set email alerts
|

The rise of hyper‐virulence

Abstract: Click here to view the Review by Weiss et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Moreover, recent studies have suggested an increased rate of MDR in hvKp species, previously identified predominantly in nosocomial cKp infections [ 110 , 111 ]. Thus, the CDC and the WHO declared such emerging MDR and hvKp infections as an urgent public health threat [ 112 , 113 , 114 ]. These infections may seriously complicate the course of COVID-19, especially in hvKp-endemic areas.…”
Section: Enterobacter Spp a Baumanni And...mentioning
confidence: 99%
“…Moreover, recent studies have suggested an increased rate of MDR in hvKp species, previously identified predominantly in nosocomial cKp infections [ 110 , 111 ]. Thus, the CDC and the WHO declared such emerging MDR and hvKp infections as an urgent public health threat [ 112 , 113 , 114 ]. These infections may seriously complicate the course of COVID-19, especially in hvKp-endemic areas.…”
Section: Enterobacter Spp a Baumanni And...mentioning
confidence: 99%